A rare primary pulmonary tumor in children; Rhabdomyosarcoma - (:unkn) unknown (My University, 2010)
After 4 cycles of chemotherapy to treat a locally advanced tumor CT showed minimal regression of the tumor. As the locally advanced tumor was still adjacent to vital structures at the 12th week of chemotherapy, radiation therapy was given to achieve local control. The treatment was stopped after 3 additional VAC courses following radiotherapy because of continued tumor progression. The patient died nine months after the initial diagnosis. We discussed prognostic features of primary pulmonary RMS and recommend that it should be considered in the differential diagnosis of children with persistent pulmonary symptoms or chest X-ray abnormalities.
Keywords: Child; Primary; Pulmonary; Rabdomyosarcoma